Stereo- and regiodefined DNA-encoded chemical libraries enable efficient tumour-targeting applications - Favalli, N; Bassi, G; Pellegrino, C; Millul, J; De Luca, R; Cazzamalli, S; Yang, S; Trenner, A; Mozaffari, NL; Myburgh, R; Moroglu, M; Conway, SJ; et al. (Nature Research, 2021)
The encoding of chemical compounds with amplifiable DNA tags facilitates the discovery of small-molecule ligands for proteins. To investigate the impact of stereo- and regiochemistry on ligand discovery, we synthesized a DNA-encoded library of 670,752 derivatives based on 2-azido-3-iodophenylpropionic acids. The library was selected against multiple proteins and yielded specific ligands. The selection fingerprints obtained for a set of protein targets of pharmaceutical relevance clearly showed the preferential enrichment of ortho-, meta- or para-regioisomers, which was experimentally verified by affinity measurements in the absence of DNA. The discovered ligands included novel selective enzyme inhibitors and binders to tumour-associated antigens, which enabled conditional chimeric antigen receptor T-cell activation and tumour targeting.